Playing "Walk And Stop" and Expressive Writing to Reduce Children's Stress During the Covid Pandemic 19 - Syiddatul Budury; Khamida Khamida (Indonesian Journal of Cultural and Community Development, 2021)
Covid-19 pandemics occurs all over the world forcing children to study and play at home. Staying at home for a long time is a risks to the occurance of stress due to limited physical activity, children are more often watching TV or playing gadgets. To reduce stress and boredom and to improve children's body movements, it is necessary to do walk and stop playing activity and expressive writing which can decrease stress and increase not only concentration but also reflexes of a child's body. This activity was attended by 16 children aged 6-12 years old at Al Rasyid Alquran Learning Center, Bangkalan. The activities was held for two days. In day one, the children wrote expressively in a book about knowing children feeling. In day two, they played walk and stop. Their stress level measured by using perceived stress scale for children. In pre test, 14 children was in mild stress level while in post test, 8 children was in mild stress level. The result of this activities indicates that children's stress is decreased. Children and parents are expected to talk to each other more and to do physical activites together so that the children can develop and grow healthy.